A presunção de veracidade atribuída ao testemunho policial: uma análise dos casos de tráfico de drogas julgados pelo TJ/PA - RIBEIRO, Ana Júlia Ferreira (2024)
The aim of this monograph is to investigate the use of testimonial evidence by police officers in drug trafficking cases, focusing on decisions by the Pará State Court of Justice (TJPA). This is because it is necessary to consider that in criminal proceedings, evidence is a central element for the parties to exercise their constitutionally guaranteed rights, such as full defense and adversarial proceedings, and thus there is a need for the evidentiary framework that underpins the court's decision to be robust enough so that there are no doubts as to the validity of the sentence. In this context, in the context of drug trafficking cases, testimonial evidence is particularly important, because it is common practice in drug trafficking cases for the public security agents who carried out the act to be listed as the only witnesses, and in many cases this evidence is sufficient to prove the perpetrator's guilt in court, based on the understanding that the testimony of police officers is presumed to be true. In this way, the research questions whether this presumption of veracity, which places police testimony in a position of greater credibility in relation to other testimonies, including that of the accused, is in line with the constitutional principles that underpin due process of law. To this end, the research presents in its first chapter a doctrinal and legislative analysis of evidence in criminal proceedings, observing the different ways in which it is applied within different legal systems, focusing on the accusatory system, as well as relating the construction of the evidentiary framework to the establishment of a criminal process that is in line with the constitutional outlines, dealing with testimonial evidence and its controversies within this system of evidence. The second chapter deals with the historical process of the institution of prohibitionism, highlighting the legal evolution of prohibitionism in Brazil and the historical context of the enactment of the current Drug Law, mainly highlighting the configuration of the crime of drug trafficking and the debate on the distinction between trafficker and user. Finally, the last chapter examines the roots of the presumption of veracity of police testimony, carrying out a jurisprudential analysis of judgments with claims of insufficient evidence in drug trafficking cases judged by the Court of Justice of the State of Pará, examining how the court positions itself when police testimony is the only means of proof.